Effect of Activated Carbon from Coconut Shells on Ammonia Concentration in Laying Hen Manure - Sara, Urfiana; Azhar, Muhammad; Aryawiguna, Muhammad Irfan; Musarianto, Musarianto; Risanta, Muhammad Iqbal (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This research aimed to determine the response of activated carbon from coconut shells to releasing ammonia in the manure of laying hens. Thirty-six 70-week-old Isa Brown strain laying hens were utilized for each treatment in this investigation. The manure was collected in the morning. A total of 50 grams of laying hen manure were gathered. Activated carbon is then sprinkled over the collected manure. Activated carbon-sprinkled manure is kept for seven days. Activated carbon application was split into four treatments. The coconut shells-activated carbon (K) treatments were applied at doses of 0%, 10%, 20%, and 30%. The measurements include shrinkage, pH, ammonia levels, and a manure smell test. The results of this study indicate that adding different amounts of activated carbon made from coconut shells to laying hens' manure can increase shrinkage, lower pH and ammonia levels, and mask the smell of the manure—especially when using 20% Coconut Shells-Activated Carbon (K2). Based on these findings, applying 20% activated carbon derived from coconut shells is recommended for optimal manure management.